1986
DOI: 10.1128/jb.166.2.385-391.1986
|View full text |Cite
|
Sign up to set email alerts
|

Lysogenic conversion of staphylococcal lipase is caused by insertion of the bacteriophage L54a genome into the lipase structural gene

Abstract: Staphylococcus aureus PS54 manifests no lipase (geh) activity. This is due to the insertion of bacteriophage L54a DNA into the geh structural gene. The nucleotide sequence of this 2,968-base-pair DNA fragment was determined. Lipase deduced from the nucleotide sequence is a polypeptide of 690 amino acids which extends from nucleotide 706 to 2776.Many strains of staphylococci produce a true lipase or glycerol ester hydrolase (EC 3.1.1.3). The activity of the staphylococcal lipase gene is negatively regulated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(106 citation statements)
references
References 29 publications
3
103
0
Order By: Relevance
“…which have also been investigated (Dring & Fox, 1983;Bozoglu et al, 1984;Kugimiya et al, 1986;Stuer et al, 1986;Lee & Iandolo, 1986;Yamamoto & Fujiwara, 1988;Aoyama et al, 1988;van Oort et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…which have also been investigated (Dring & Fox, 1983;Bozoglu et al, 1984;Kugimiya et al, 1986;Stuer et al, 1986;Lee & Iandolo, 1986;Yamamoto & Fujiwara, 1988;Aoyama et al, 1988;van Oort et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa EF2 lipase is strikingly similar to that of the other Pseudomonas lipases which have recently been sequenced, either by direct analysis of the purified enzymes or from the DNA sequences of the lipase genes (Kugimiya et , 1986), it must be concluded that these two enzymes contain a non Nterminal deletion and addition, respectively. It should be noted that none of the Pseudomonas lipases show any Nterminal sequence similarity to the lipases from S. aureus and S. hyicus (Lee & Iandolo, 1986 ;van Oort et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integrated loci were transferred into RN6390 by 11-mediated transduction, producing strains designated KB700, KB707, KB706, and KB705 that were used for reporter gene assays (Table 1). Proper integration of the promoter fusion constructs was confirmed by Southern blot analysis and/or PCR analysis using the 5Ј primer employed for the production of the promoter fragment along with a second oligomer (5Ј-GTTCTGCACCTTTACGTTG-3Ј) that is complementary to a DNA sequence downstream of the attB integration site within the geh locus (19).…”
Section: Methodsmentioning
confidence: 99%
“…The enterotoxin A gene which is associated with a converting bacteriophage (Betley & Mekalanos, 1985) maps in interval 6 (Pattee & Glatz, 1980) but can occupy other chromosomal sites (Mallonee et al, 1982). The a-toxin (hly) and lipase (geh) genes were inactivated with drug resistance insertion mutations isolated by allele replacement (O'Reilly et al, 1986) and plasmid integration (Lee & Iandolo, 1986), respectively. The integrated drug resistance determinants served as selective markers for the virulence factor loci in mapping experiments (Pattee, 1986(Pattee, , 1987.…”
Section: Introductionmentioning
confidence: 99%